Exploring the Significance of Abdominal Drawing-in and Segmental Stabilisation Training (SST) for Low Back Pain Management - Rasim ul Hasanat; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
Segmental Stabilisation Training (SST) a programme initially conceived by Carolyn Richardson and her team, serves as a specialised approach tailored to alleviate mechanical low back pain. Built upon decades of rigorous research, this exercise model rests upon the foundational principles of core stability. SST is unique due to its singular focus on addressing the root cause of low back pain, thereby presenting a promising avenue for averting the frequent relapses characteristic of this condition. Many fitness regimens that emphasize core stability incorporate the Abdominal Drawing-in manoeuver. However, the efficacy of this technique often remains unrealized due to a lack of awareness regarding its correct execution. It is imperative to note that the true benefits of the Abdominal Drawing-in manoeuver manifest only when performed accurately, ensuring the activation of deep core muscles and, in turn, preventing the recurrence of low back pain. The SST programme offers clear and precise guidance, enabling both clinicians and patients to acquire the requisite skills for its correct implementation. This minireview highlights the significance of SST in low back pain management and also elucidates the crucial role of precise technique execution. Keywords: Low Back Pain, Exercise Therapy, Core Stability, Exercise Movement Technique, Physical Therapy Specialty, Physical and Rehabilitation Medicine.